The Influence of Knowledge Management and Competence on Innovation Performance of Village-Owned Enterprises Mediated by Motivation - Waris, Waris (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyse the impact of knowledge management and competence on innovation performance in Village-Owned Enterprises (BUMDesa), with motivation as a mediating variable. Using a quantitative approach, data were collected from 125 respondents through questionnaires and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). This study contributes original insights by presenting a comprehensive analysis of the relationship between knowledge management, competence, and innovation performance in the context of BUMDesa, particularly through the role of motivation as a mediating variable that has been rarely explored. The results indicate that knowledge management has a positive and significant impact on innovation performance; however, this impact is not mediated by motivation. Meanwhile, competence was found to have a direct positive influence on innovation performance and also influences it indirectly through increased motivation. Thus, improving individual competence not only has a direct impact on innovation but also enhances motivation, which ultimately supports innovation performance. This study concludes that knowledge management will be more effective if directly focused on improving innovation performance, while competency development can be used as a strategy to enhance motivation and promote sustainable innovation in the BUMDesa environment.